Small-Sized Tomato Pomace: Source of Bioactive Compounds and Ingredient for Sustainable Production of Functional Bread - Selina Brighina; Luana Pulvirenti; Laura Siracusa; Elena Arena; Maria Veronica Faulisi; Cristina Restuccia (Foods)
Tomato processing generates a by-product known as tomato pomace (TP), which contains chemically diverse valuable components such as lycopene, phenols, dietary fibre, proteins, and oil. The aim of this study was to characterize bioactive compounds in small-sized tomato pomace from cherry and date tomatoes and to evaluate the effects of the addition of 10 and 20% (w/w) of tomato pomace flour (TPF) to durum wheat dough for bread production. Bread containing different amounts of TPF was characterized by physical, chemical, nutritional, and sensory characteristics. TPF is an important source of dietary fibre with a total content of approximately 52.3%, of which 5.3% is soluble and 47% is insoluble. It is also a potential source of natural antioxidants and contains remarkable residual levels of both total carotenoids and polyphenols. TPF addition reduced water loss during baking and significantly affected colour parameters and acidity; furthermore, both fortified TPF breads could use these nutrition and health claims and label the breads as “High Fibre”. The “overall” sensory attribute showed similar values in the control and fortified bread samples, suggesting that the overall quality of the bread remained relatively constant, regardless of the percentage of added TPF.